Echocardiography in Adult Congenital Heart Disease - Li, Wei; Henein, Michael; Gatzoulis, Michael A. (Springer London : Imprint: Springer, 2007)
Congenital heart disease is a multi-faceted and complex subject due to the immense variability in cardiac morphology. Some of these changes can be expected as part of the natural history of the various diseases and others are directly related to the original surgery correcting the congenital defect, so it has become clear that adult congenital cardiology is a defined entity on its own. Cardiologists and cardiac radiologists therefore must be prepared for a huge variability in the echocardiographic appearances of congenital heart disease both pre and postoperative, and this book provides the tools to evaluate the potential malformed pediatric or adult heart. Echocardiography in Adult Congenital Heart Disease provides the cardiologist with access to the considerable wealth of imaging data from Royal Brompton Hospital and National Heart and Lung Institute in London, UK. Consequently, the book contains numerous echocardiographic images to illustrate the appearances of rare defects and demonstrates areas for using non-invasive imaging to assess cardiac physiology in different disease. This gives readers a practical insight into the techniques needed to establish non-invasive diagnoses of congenital heart diseases.